Examination of Long-Term Diseases, Conditions, Self-Control, and Self-Management in Kidney Transplant Recipients - Zuleyha Simsek Yaban; Semra Bulbuloglu (Transplantology)
Objective: This study aims to examine long-term diseases, conditions, self-control, and self-management in kidney transplant recipients. Method: This is a descriptive correlational study, including a total of n = 130 kidney transplant recipients. The data were collected using a demographic information form, the Post-Kidney Transplant Diseases and Conditions Assessment Form, and the Self-Control and Self-Management Scale. Data analysis was conducted using descriptive statistical methods and one-way ANOVA, and paired sample t-tests. Results: Of the kidney transplant recipients, 40% were aged between 31 and 45 years, and 54.6% were male. The long-term diseases and conditions they developed after kidney transplantation were hypertension (46.2%), heart failure (26.2%), diabetes mellitus (10.8%), heartburn (35.4%), acute kidney failure (26.2%), urinary tract infection (39.2%), sleep disorders (23.1%), and chronic pain (50%). In addition, 31.5% of the kidney transplant recipients had poor self-control and self-management. Conclusions: Long-term postoperative mortality in kidney transplant recipients is mostly caused by diseases developing in vital organs. Therefore, it is crucial to recognize these diseases and conditions for their diagnosis. This study found various diseases and conditions in almost all body systems of kidney transplant recipients. Additionally, there were patients with poor self-control and self-management. We consider that the results of our study will increase awareness among clinicians.